Pengaruh Fear Of Missing Out (FOMO) dan Promosi Digital Terhadap Keputusan Pembelian Konsumen pada Produk Iphone (Studi Pada Mahasiswa di Kota Medan) - Pardede, Rachel Natasia; Hafiza, Hafiza; Siregar, Onan Marakali (Universitas Serambi Mekkah, 2024)
The development of the internet and social media has become one of the important parts of daily life both in the business sector and other sectors. The advancement of the internet is used by business people to promote their products online through various social media. Another impact caused by the development of social media, especially among teenagers, is the emergence of the FOMO. phenomenon. FOMO is a psychological phenomenon that arises due to the fear and anxiety of individuals to miss something that can affect their shopping behavior. Therefore, these two things have an influence to encourage consumers to buy a product. This study aims to determine the influence of FOMO and digital promotion on consumer purchase decisions in students who use iphone products in Medan. This study used a quantitative with an associative approach. The population in this study is students who use iPhone products in Medan City with a sample of 96 respondents. The sample approach used in this study is non-probability sampling in the form of purposive sampling. Primary data was obtained through the distribution of questionnaires directly and secondary data was obtained through literature studies. The analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression, partial test, simultaneous test, and determination test and processed with SPSS software. The results showed that FOMO has a significant positive effect on consumer purchase decisions with a total tcal value of 6.558 1.985 with a sig value of 0.000 0.05 and has a regression coefficient value of 0.608. Digital promotion also has a significant effect on purchase decisions with a tcal value of 2.436 1.985 with a sig value of 0.017 0.05 and has a regression coefficient value of 0.197. In the simultaneous test, the variables of FOMO and digital promotion had an effect simultaneously with the magnitude of influence of 34.4% while 65.6% was influenced by factors outside this study.